2022
DOI: 10.1097/ana.0000000000000871
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Unplanned Post-Craniotomy Re-intubation in Children: A NSQIP-Pediatric® Analysis

Abstract: Objective: Most children undergoing craniotomy with general endotracheal anesthesia are extubated postoperatively, but some require unplanned postoperative intubation (UPI). We sought to determine the incidence of UPI and identify associated factors and related postoperative mortality. Methods:The National Surgical Quality Improvement Program for Pediatrics (2012)(2013)(2014)(2015)(2016)(2017)(2018) was used to retrospectively identify patients less than 18 years old who underwent craniotomy for epilepsy, tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It has been reported that nearly 5% of adult patients require reintubation following craniotomy, most commonly due to neurologic deterioration [ 6 ]. Tracheal reintubation following craniotomy in pediatric patients is relatively rare with a reported rate of 0.94%; however, odds of reintubation are higher in patients 1-5 years of age and following procedures involving the posterior fossa [ 7 ]. Following VP shunt placement, our patient was successfully extubated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that nearly 5% of adult patients require reintubation following craniotomy, most commonly due to neurologic deterioration [ 6 ]. Tracheal reintubation following craniotomy in pediatric patients is relatively rare with a reported rate of 0.94%; however, odds of reintubation are higher in patients 1-5 years of age and following procedures involving the posterior fossa [ 7 ]. Following VP shunt placement, our patient was successfully extubated.…”
Section: Discussionmentioning
confidence: 99%